Brand Image and Customer Loyalty of Parents in a Private Sectarian School in Central Negros - Romatico, Analyn F.; Menes, Carmen C. (Philippine Social Science Journal, 2025)
This quantitative study investigated the relationship between brand image and customer loyalty among parents at a private sectarian school in Central Negros Occidental to inform strategic marketing. Using a researcher-made questionnaire, the analysis revealed that a strong brand image significantly correlates with high parental loyalty across all demographics, although opportunities exist to improve perceptions of competence and benefits, particularly for lower-income families. These findings underscore the practical value of strategic branding in driving retention and institutional growth. Consequently, future research should explore the long-term sustainability of this relationship, the impact of specific educational policies, and the perspectives of broader stakeholder groups through longitudinal analysis.